Irony and refutation: the elenchos of Callicles in Plato ́s Gorgias - Forciniti, Martín (Revista Archai, 2022)
In this work I use the concept of irony to analyze the elenchos that Socrates practices on the opinions of Callicles in the Gorgias. I assume as a starting point that Socrates aims at the modification of his interlocutor ́s animic disposition, adopting a philosophical way of life and abandoning the rhetorical one. To do this, he develops an ironic elenchos that has three moments: a feigned acceptance by Socrates of the dichotomy presented by Callicles between the life of the politician, worthy of imitation, and that of the philosopher, worthy of reproach; a reversal of that dichotomy; and finally, a questioning of that reversal. I will conclude by arguing that this third moment constitutes a new Socratic maneuver to urge Callicles to suspend his political activities, and previously examine philosophically with him the way to become virtuous.